2021
DOI: 10.1021/acsami.0c17729
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hafnium Zirconium Oxide Interfacial Band Alignments Using Internal Photoemission Spectroscopy and X-ray Photoelectron Spectroscopy

Abstract: Doped ferroelectric HfO2 is highly promising for integration into complementary metal-oxide semiconductor (CMOS) technology for devices such as ferroelectric nonvolatile memory and low-power field-effect transistors (FETs). We report the direct measurement of the energy barriers between various metal electrodes (Pt, Au, Ta, TaN, Ti/Pt, Ni, Al) and hafnium zirconium oxide (Hf0.58Zr0.42O2, HZO) using internal photoemission (IPE) spectroscopy. Results are compared with valence band offsets determined using the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Both top and bottom φ bn values are within the 2.5−3.0 eV range reported by Jenkins et al for bottom ALD HZO/TaN barriers with a variety of top electrode metals. 20,26 For their TaN/HZO/TaN devices, Jenkins et al measured 2.7 eV for the top TaN/HZO barrier, within error of our result, but only 2.5 eV for the bottom HZO/TaN barrier, substantially less than the 2.9 eV seen here. The difference is likely due to differences in processing.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Both top and bottom φ bn values are within the 2.5−3.0 eV range reported by Jenkins et al for bottom ALD HZO/TaN barriers with a variety of top electrode metals. 20,26 For their TaN/HZO/TaN devices, Jenkins et al measured 2.7 eV for the top TaN/HZO barrier, within error of our result, but only 2.5 eV for the bottom HZO/TaN barrier, substantially less than the 2.9 eV seen here. The difference is likely due to differences in processing.…”
Section: Resultssupporting
confidence: 78%
“…IPE spectroscopy is an optoelectronic technique that involves measurements of current in a biased device while under simultaneous ultraviolet illumination. ,, A previous comparison of XPS and IPE measurements on a similar materials system has shown that XPS measurements are insensitive to trapped charge, which is known to play critical roles in the operation of HZO MFM devices . HZO in as-fabricated devices tends to be primarily in the nonferroelectric monoclinic, tetragonal, or antipolar orthorhombic crystal structures. Inducing ferroelectric behavior in HZO devices (waking) often requires repeated electric field cycling. It is thought that the field cycling during waking induces the transformation of nonferroelectric tetragonal and/or antipolar orthorhombic phases to the ferroelectric orthorhombic phase and possibly the formation or redistribution of charged defects (most likely oxygen vacancies, which will be generically termed V O + unless specific charge states are discussed). ,, Subsequent “poling” of the devices via application of a single 100× longer positive or negative unipolar pulse aligns the ferroelectric domains and sets the polarization state to either P↓ (positive bias on top electrode) or P↑ (negative bias on top electrode). It is also thought that the relatively long duration stress during the poling process involves the creation of V O + and/or drift of V O + to one of the electrode interfaces. , Due to the potential involvement of charged defects and the creation and flipping of ferroelectric (FE) domain dipoles, both the waking and poling processes might be expected to impact the energy barriers at the HZO/electrode interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…E gap [eV] 5.7-6 [ 30,[35][36][37] 5.2-5.4 [ 8,31,[37][38][39][40] Electron affinity 𝜒 [eV] 2.2-2.5 [ 35,36,41] 2.2 [39] E CNL -E VBM [eV] 3.64-3.9 [ 22,41,42] -FL pinning factor S 0.67-0.7 [ 30,43] 0.8 ± 0.05 [31] V •• E def -E CBM (eV) 0.6-1.2 [ 11,[44][45][46][47] which can be reformulated into the well-known FLP equation [22,29,30]…”
Section: Hfo 2 Hzomentioning
confidence: 99%
“…The band gap of HZO is reported to be about 0.2-0.4 eV smaller than for HfO 2 . [31][32][33] For the electron affinity, it has to be noted that values of 1.75 and 2.9 eV [34] are reported as well, which are far out of the commonly considered range as tabulated. It also should be pointed out that the published CNLs, as listed, are frequently referenced to the valence band maximum (VBM), whereas Φ CNL in Equations ( 2) -( 6) is referred to the vacuum level (see Figure 1).…”
Section: Hfo 2 Hzomentioning
confidence: 99%
“…In 1984, Marcel Pourbaix proposed hafnium as a metal to be considered for surgical implants due to the passive state of the metal with properties like high ductility, strength, resistance to corrosion, and mechanical damage. Various in vitro studies were conducted on hafnium metal [33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%